DETERMINANTS OF POVERTY IN FIVE REGENCIES OF EAST JAVA PROVINCE - Noor Shania Wardaningrum; Putu Ayu Pramitha Purwanti (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Poverty remains one of the main challenges in achieving sustainable economic development, particularly in regions with high industrial potential but persistent poverty rates. East Java Province is recognized as one of Indonesia’s leading manufacturing hubs; however, several regencies still record relatively high poverty levels. This study aims to analyze the effects of the manufacturing sector’s contribution, the Human Development Index (HDI), district minimum wages (UMK), and the open unemployment rate (OUR) on poverty levels in five key industrial regencies—Malang, Pasuruan, Mojokerto, Tuban, and Gresik—over the period 2014–2023. Panel data regression with a Fixed Effects Model (FEM) approach was employed. The findings reveal that, simultaneously, all four independent variables significantly affect poverty levels. Partially, only HDI exerts a negative and significant influence, while the manufacturing sector contribution, UMK, and OUR show no significant effect. These results underscore that improving quality of life through HDI enhancement is more effective in reducing poverty than relying solely on manufacturing sector growth. Therefore, poverty alleviation policies should prioritize human capital development and equitable distribution of economic benefits at the regional level.